Proceedings of the 8th ACM/IEEE International Symposium on Empirical Software Engineering and Measurement 2014
DOI: 10.1145/2652524.2652546
|View full text |Cite
|
Sign up to set email alerts
|

Forking and coordination in multi-platform development

Abstract: Context]With the proliferation of desktop and mobile platforms the development and maintenance of identical or similar applications on multiple platforms is urgently needed.[Goal] We study a software product deployed to more than 25 software/hardware combinations over 10 years to understand multi-platform development practices.[Method] We use semi structured interviews, project wikis, VCSs and issue tracking systems to understand and quantify these practices.[Results]We find the projects using MR cloning, MR r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Researchers have recognized awareness as an essential success factor of collaborative software development. For example, the investigation of Duc et al (2014) on multi-platform development practices showed that diverged code bases frequently lead to redundant development. Our approach can be used to develop an understanding of changes at the level of features in distributed development.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers have recognized awareness as an essential success factor of collaborative software development. For example, the investigation of Duc et al (2014) on multi-platform development practices showed that diverged code bases frequently lead to redundant development. Our approach can be used to develop an understanding of changes at the level of features in distributed development.…”
Section: Related Workmentioning
confidence: 99%
“…Evaluation metrics are used extensively in empirical study about data mining, software quality predictions and software metrics. We adopted the set of evaluation metrics in our previous work [37,38]. These metrics are also successfully adopted in studies about security before [13,20] It is possible to have both TP and FP in a test file.…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…The Android software chosen for this study is a fork of the Spark codebase. A more in-depth description of the development process is provided in [17].…”
Section: Software Descriptionmentioning
confidence: 99%